Application of eco-friendly cationic celluloses for effective sludge dewatering - Menon, Snehal; Suresha, P. R.; Khairnar, Ajay; Kalyanraman, V. (Water Air and Soil Pollution, 2024)
The study presents the application of cationic celluloses in sludge dewatering. The source of cellulose used in this study were microcrystalline cellulose and alkaline-treated rice straw. The cationic celluloses were synthesized in a two-step reaction involving oxidation of cellulose with sodium periodate and followed by Schiff base reaction with Girard reagent T to introduce quaternary ammonium cations. The functional groups and chemical structure were confirmed by FTIR and NMR spectroscopy. The molecular weight and cationicity index of cationic cellulose were determined. Owing to their low molecular weight, the cationic celluloses functioned as coagulants and brought about charge neutralization through electric patches. The cationic celluloses were effective in promoting rapid sludge settling and improving the sludge filterability. The cationic celluloses are eco-friendly and non-toxic alternatives to acrylamide-based flocculants.
Keywords: biodegradable; Cationic cellulose; coagulation; Sludge dewatering; Wastewater treatment